Integrating Islamic Values and Modern Pedagogy: A Systematic Review of PAI Curriculum Development in School - Abadi, Sri Bintang; Toyibah, Putri Salisatu; Alfadhillah, Khoirunnisa; Erihadiana, Mohamad (LifeSciFi, 2025)
This research is motivated by the demand for changes in educational policy through the Merdeka Curriculum, which encourages the development of an adaptive, relevant, and Islamic Religious Education (PAI) curriculum in madrasah and schools. The purpose of this study is to systematically examine various research results related to the development of the PAI curriculum and its relationship to the Merdeka Curriculum policy and the direction of development based on Islamic values. The method used is a Systematic Literature Review by combining thematic qualitative analysis and bibliometric analysis using VOSviewer. Data searches were conducted through the Publish or Perish application with four main keywords and a limit of 20 articles per keyword, resulting in 80 initial articles which were then selected using the PRISMA stage until 20 relevant articles remained. The research findings show that the theme of PAI curriculum development is dominated by the keywords curriculum development, Islamic education, PAI, Merdeka curriculum, education, and Islam, with curriculum development as the highest network center. In conclusion, the development of the PAI curriculum demonstrates a paradigm transformation that is adaptive to national policy, responsive to digitalization, and rooted in Islamic values.